(untitled) (CIPEEX, 2026)
Introduction: Low back pain is one of the most prevalent health conditions worldwide, with substantial personal, professional, social, and economic consequences. In Brazil, data from the 2019 National Health Survey (PNS), conducted by the Brazilian Institute of Geography and Statistics (IBGE), reported chronic back pain (CBP) in 21.6% of adults, with higher prevalence among women (24.5%). Objective: To evaluate muscle activity using surface electromyography in individuals with chronic low back pain following dry needling treatment. Methods: A clinical trial was conducted at the Evangelical University of Goiás with 21 volunteers aged 18–40 years, randomized into two groups: Group 1 (Dry Needling) and Group 2 (Sham). Surface electromyography was used to assess the electrical activity of the multifidus and iliocostalis muscles. The intervention consisted of a 15-minute application of dry needling (G1) or sham (G2). Statistical analyses included the Mann-Whitney test, repeated-measures ANOVA, and effect size calculation (p<0.05). Results: No significant differences were found between groups or across assessment times (p>0.05). During task execution under simple conditions, neuromuscular activation of the iliocostalis and multifidus muscles did not differ significantly between groups ([F = 0.204; p = 0.652] and [F = 1.681; p = 0.199], respectively), with a small effect size (d < 0.2 for both muscles). Conclusion: Dry needling was not superior to sham treatment, underscoring the need for studies with larger samples and more targeted interventions. Keywords: Low Back Pain; Electromyography; Dry Needling; Physical Therapy.